PENERAPAN PERMAINAN KECIL BENTENG-BENTENGAN UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN PJOK DI SMK HARAPAN BANGSA KOTA SERANG - Ade Restu Maulana; Desty Subroto; Muhamad Saeza; Nadya Rahayu; Ahmad Hujaimi; Reva Anwar Marsela (Jurnal Padamu Negeri, 2025)
Learning is a system that involves an integrated set of interrelated and interactive components to achieve expected results optimally, with predefined goals. Physical Education, Sports, and Health (PJOK), for example, encourages students to move actively to reach the goal of improved physical fitness. PJOK does not require students to always be able and skilled at practicing the material; rather, it emphasizes the willingness, desire, and success in actively moving or participating in learning activities. Active participation can increase when the learning process is engaging, exciting, non-monotonous, innovative, and creative. This can be achieved by incorporating small games, such as the traditional "fort" game (benteng-bentengan). The purpose of this research is to measure the impact of implementing small games on increasing active student participation in PJOK classes for 11-grade students at SMK HARAPAN BANGSA KOTA SERANG. This research employs a pure experimental method with a quantitative approach, using a randomized control group pretest-posttest design. The sample consists of 28 students in the control group and 24 students in the treatment group. Data were collected through video analysis using the Proportion Focus Analysis (APF) instrument. Statistical calculations conducted using the Statistical Package for the Social Sciences (SPSS) showed a significant value in the Wilcoxon test of 0.009, which is less than 0.05. This result indicates that implementing the "fort" game has a positive effect on increasing active student participation in PJOK classes at SMK HARAPAN BANGSA KOTA SERANG.